Experimental Hydraulic Device for the Testing of Hydraulic Pumps and Liquids - Z. Tkáč; J. Kosiba; Ľ. Hujo; J. Jablonický; J. Nosian (Tribology in Industry, 2018)
The goal of this paper is the verification measurement of the proposed laboratory testing device for operation monitoring and assessment of both the hydraulic circuit components and the energy carrier used. The goal is to test the operation of a proposed hydraulic circuit within the range of selected working pressures, flows and working fluid temperatures using the QHD-17R tractor hydraulic pump, which is used in hydraulic drive systems of agricultural and forestry tractors. By the verification measurement, we proved that the proposed laboratory testing device is suitable for testing hydraulic circuit components, as well as, potentially, for testing and monitoring the changes in physical properties of hydraulic fluids.